2014
DOI: 10.1371/journal.pone.0093375
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Diversity of Resting-State Fluctuations in the Human Brain

Abstract: In order to assess whole-brain resting-state fluctuations at a wide range of frequencies, resting-state fMRI data of 20 healthy subjects were acquired using a multiband EPI sequence with a low TR (354 ms) and compared to 20 resting-state datasets from standard, high-TR (1800 ms) EPI scans. The spatial distribution of fluctuations in various frequency ranges are analyzed along with the spectra of the time-series in voxels from different regions of interest. Functional connectivity specific to different frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 25 publications
6
61
0
Order By: Relevance
“…The reduction of slow-5 fALFF was likely not due to changes at the higher frequencies (0.073-0.192 Hz), as power in those frequencies is minimal. This was demonstrated in this study as well as in prior studies (Calhoun Zuo et al, 2010), Furthermore, low-TR fMRI (Kalcher et al, 2014) and MR-Encephalography (Lee et al, 2013) studies, techniques offering much improved temporal resolution, also confirmed the small contributions of high oscillations during the resting state.…”
Section: Discussionsupporting
confidence: 89%
“…The reduction of slow-5 fALFF was likely not due to changes at the higher frequencies (0.073-0.192 Hz), as power in those frequencies is minimal. This was demonstrated in this study as well as in prior studies (Calhoun Zuo et al, 2010), Furthermore, low-TR fMRI (Kalcher et al, 2014) and MR-Encephalography (Lee et al, 2013) studies, techniques offering much improved temporal resolution, also confirmed the small contributions of high oscillations during the resting state.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in this work, we simply establish the feasibility of multiband imaging as a viable method to investigate rs-fMRI physiology. While slice-accelerated imaging offers alluring potential and its reliability in multiple applications has been tested (Kalcher et al, 2014;Xu et al, 2013) it will need to undergo further tests of time. Fig.…”
Section: Potential Caveatsmentioning
confidence: 99%
“…The observed distributions of node degree and relative Fourier amplitude of low-frequency activity are in close agreement with existing reports considering the two parameters separately and are unlikely to be driven primarily by noise. [13][14][15][16]18,28,29,37,61 This spectral heterogeneity points to different dynamics of underlying neural activity. Even though BOLD signals are not well-suited for non-linear dynamical analysis due to short time-series length, undersampling, physiological noise, and confounds from neurovascular coupling, we attempted Figure 4(a) for network diagram).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Recent increases in the sampling rate of functional MRI have made it possible to study inter-regional spectral differences, often represented with power-law frequency scaling coefficients or relative Fourier amplitudes of low frequencies (typically <0.1 Hz). 19,28,29 At the same time, the fact that realistic RSNs emerge even in highly simplified simulation scenarios, for example, from networked phase (Kuramoto) oscillators or discrete excitable units, raises the intriguing possibility of recapitulating some dynamical phenomena underlying brain function in other physical systems, where direct manipulation of connectivity is possible and causal relationships between connectivity and non-linear dynamics can be explored experimentally. [8][9][10]30 In particular, it has recently been shown that singletransistor oscillators can exhibit strikingly complex activity depending on an easily tunable control parameter (DC voltage source series resistance), oscillating periodically, chaotically, or close to criticality.…”
Section: Introductionmentioning
confidence: 99%